2020
DOI: 10.1093/cid/ciaa888
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in Healthcare Personnel With High-risk Occupational Exposure: Evaluation of 7-Day Exclusion From Work Policy

Abstract: Background Starting in late February 2020, Greece is experiencing a coronavirus disease 2019 (COVID-19) epidemic. Healthcare personnel (HCP) were disproportionately affected, accounting for approximately 10% of notified cases. Exclusion from work for 7 days was recommended for HCP with high-risk occupational exposure. Our aim was to evaluate the 7-day exclusion from work policy for HCP with high-risk exposure. Methods HCP wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
82
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 22 publications
8
82
3
5
Order By: Relevance
“…The 9.2% infection rate we observed among HCWs with high-risk exposures is consistent with previously published data. 6,7 However, our finding differs in demonstrating a full gradient of risk, with infection rates associated with medium-risk exposures intermediate between low-and high-risk groups. The observed "dose response" between exposure severity and infection rates suggests a causal relationship during the study timeframe.…”
Section: Discussioncontrasting
confidence: 57%
“…The 9.2% infection rate we observed among HCWs with high-risk exposures is consistent with previously published data. 6,7 However, our finding differs in demonstrating a full gradient of risk, with infection rates associated with medium-risk exposures intermediate between low-and high-risk groups. The observed "dose response" between exposure severity and infection rates suggests a causal relationship during the study timeframe.…”
Section: Discussioncontrasting
confidence: 57%
“…Starting in late 2019, the world is faced with a pandemic of a respiratory disease named coronavirus disease 2019 (COVID-19) which is caused by a novel beta-coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 1 ]. Healthcare personnel (HCP) have been recognized as a high-risk group for SARS-CoV-2 infection [ [2] , [3] , [4] ], as also shown during the epidemics of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome [ 5 , 6 ]. During the first SARS-CoV-2 epidemic wave in Greece HCP accounted for approximately 10% of notified cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare personnel (HCP) have been recognized as a high-risk group for SARS-CoV-2 infection [ [2] , [3] , [4] ], as also shown during the epidemics of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome [ 5 , 6 ]. During the first SARS-CoV-2 epidemic wave in Greece HCP accounted for approximately 10% of notified cases [ 2 ]. Herein, we estimate the risk of infection among HCP by hospital characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Maltezou et al. observed that administrative personnel were more likely to get infected in hospital than front-line workers, suggesting that administrative staff were less trained in the use of PPE [ 6 ]. Lockdown commenced in France on 17 th March 2020.…”
mentioning
confidence: 99%